Vertikal Accuracy Assessment On Sentinel-1, Alos Palsar, And Demnas In The Ciater Basin - Ihsan, Haikal Muhammad; Sahid, Sahid Sahid (Indonesia University of Education, 2021)
Vertical accuracy in DEM (Digital Elevation Model) products is very important for an earth study. There are medium resolution DEM data products that can be accessed freely such as DEMNAS, Alos Palsar 12.5m and Sentinel-1. The aim of this study is to measure the vertical accuracy of the DEMNAS, Alos Palsar 12.5m and Sentinel-1 data products by considering the slope angle classification and using two different GIS software. Vertical accuracy is measured using 848 spotheight points, by calculating the RMSE (Root Mean Square Error) value of each DEM product with different software. Based on the research, it was found that DEMNAS is a DEM product that has the best comparability value than Alos Palsar and Sentinel-1, because it has the smallest RMSE value. Slope angle class gives different values of bias against absorption and reflection of electro magnetic waves. Flat to moderate steep slope angles tend to be better at absorbing and reflecting electromagnetic waves. Perbedaan software dalam analisis tidak terlalu mempengaruhi ketinggian titik tinggi DEM dan RMSE. The spotheight point needs to be reaccurated with a more detailed geodetic point, to get maximum results.